2022
DOI: 10.1177/23259671221092770
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cruciate Ligament Reconstruction in 107 Competitive Wrestlers: Outcomes, Reoperations, and Return to Play at 6-Year Follow-up

Abstract: Background: Wrestling is a physically demanding sport, with young athletes prone to anterior cruciate ligament (ACL) injuries. There is a paucity of data evaluating the results of ACL reconstruction (ACLR) in this cohort. Purpose: To assess return to sport (RTS), patient-reported outcomes, reoperation rates, and graft survival after ACLR in a large cohort of competitive wrestlers at midterm follow-up. Study Design: Case series; Level of evidence, 4. Methods: We identified all competitive wrestlers (club, high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Their 2022 study encompassed 64 bone-patellar tendon-bone (BTB) and 43 hamstring autografts in 103 athletes. 10 The authors reported that 80% of the patients were able to return to wrestling a median 280 days after surgery. Graft failure occurred in 14 knees at a median of 1.8 years postoperatively and was significantly more common when a hamstring graft was used.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Their 2022 study encompassed 64 bone-patellar tendon-bone (BTB) and 43 hamstring autografts in 103 athletes. 10 The authors reported that 80% of the patients were able to return to wrestling a median 280 days after surgery. Graft failure occurred in 14 knees at a median of 1.8 years postoperatively and was significantly more common when a hamstring graft was used.…”
mentioning
confidence: 99%
“…Retrospectively reviewing cases treated between 1996 and 2020, Marigi et al 9 were able to report the outcomes in 104 wrestlers: 79 with anterior instability, 14 with posterior instability, and 11 with traumatic multidirectional instability. A total of 58 athletes presented after their initial injury event, while the other 46 experienced multiple episodes of instability before being evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Compared with other sports, wrestling frequently places athletes at a high risk of sustaining various musculoskeletal injuries. 17,18,21,23 In these young athletes, the downstream sequelae of injuries include recurrent extremity complications, time away from sport, surgery, and psychosocial challenges. 5 Notably, the shoulder girdle is often susceptible to injury as it is a frequent target for the application of supraphysiological forces with or without the presence of generalized ligamentous laxity.…”
mentioning
confidence: 99%
“…The knee is particularly susceptible to injury in wrestlers owing to repetitive supraphysiologic forces applied to an athlete’s hyperflexed knees. 1,5,18,28,29 Lateral patellar dislocation is one such knee injury that commonly occurs in wrestlers. With the exclusion of anatomic risk factors such as trochlear dysplasia and patella alta, a patellar dislocation may be caused by direct contact or lateral stress on a planted foot.…”
mentioning
confidence: 99%